Is dienogest the best medical treatment for ovarian endometriomas? Results of a multicentric case control study. (2nd January 2020) - Angioni, Stefano; Pontis, Alessandro; Malune, Maria E.; Cela, Vito; Luisi, Stefano; Litta, Pietro; Vignali, Michele; Nappi, Luigi
Abstract: Ovarian endometriomas are common manifestations of endometriosis. Surgical excision has been shown to potentially decrease ovarian reserves. In this prospective study, we included 81 patients with ovarian endometriosis. 40 were treated with 2 mg of dienogest daily (DNG) and 41 were treated with cyclic oral estro-progestins (ethinyl estradiol 30 mcg [EE] plus dienogest 2 mg) (DNG + EE). Aim of the study was the effect of the treatment on the size of the endometriotic cysts. Further, in the symptomatic patients, follow-up included an evaluation of chronic pain before and during treatment. Both treatments were able to significantly decrease the pain in symptomatic patients with no statistical differences. The mean visual analog scale score at enrollment was 65 ± 14 and 70 ± 18, and there was significant improvement (19 ± 15, p  < .001, DNG; 18 ± 12, p  < .001, DNG + EE). The size of the endometrioma cysts were significantly reduced in the DNG group. The mean cyst diameter was 52 ± 22 mm at baseline and 32 ± 12 mm after six months of treatment ( p  < .001), yielding a 75% volume reduction in DNG group. The decrease in the size of endometrioma cysts observed in the women treated with only progestin could be noteworthy, as it may reduce the negative impacts on the affected ovary and avoid surgery.